Plasmonic Metasurfaces with High UV–Vis Transmittance for Photopatterning of Designer Molecular Orientations. Issue 11 (25th March 2019) - Yu, Hao; Jiang, Miao; Guo, Yubing; Turiv, Taras; Lu, Wu; Ray, Vishva; Lavrentovich, Oleg D.; Wei, Qi‐Huo
Abstract: Recent developments of utilizing plasmonic metasurfaces in photopatterning of designer molecular orientations have facilitated numerous new applications of liquid crystals; while the optical efficiency of the metamasks remains a critical issue, especially in the UV region. Here a new design of plasmonic metasurfaces made of parallelepiped arrays is presented which yield very high and broadband transmission in the UV–vis wavelength range. It is shown that this plasmonic metamask exhibits two polarization peaks originated from a cavity mode and lattice resonance respectively and demonstrated that complex designer molecular orientations can be photopatterned by using this metamask with significantly reduced exposure time. This type of high‐efficiency broadband plasmonic metasurfaces is not only important for high resolution photopatterning of molecular orientation but also tailorable for various other flat optics applications in the UV and near UV regions. Abstract : Spatially variant molecular orientations are central to many liquid crystal applications. Here a new design of plasmonic metasurfaces with ultrahigh optical transmissions as metamasks for photopatterning arbitrary designer molecular orientations is presented and it is demonstrated that such metamasks can significantly reduce the exposure time of the photopatterning.